IMAGINATIVE COMPONENT OF THE LINGUO-CULTURAL CHARACTER TYPE «BUSINESS MAN» IN RUSSIAN AND ENGLISH - Elena V. Ilyinova (Sovremennye Issledovaniâ Socialʹnyh Problem)
Background. Since the beginning of the 2000s the theory of linguo-cultural types has been developing in Russian linguistics. Still, the linguo-cultural type ‘business man’ has not yet received its comprehensive description.